Why Africa Matters to Americans - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, talked about a new generation of leaders emerging in Africa, who increasingly recognize their responsibility to their people. The landscape across Africa is changing. Conflicts diminish. Small Businesses emerge. We are seeing a new breath of hope infused in all parts of that continent. More and more Africans are saying they can’t live with corruption. Strong U.S. support for foreign aid is particularly important to help address issues important to Americans, issues like government transparency, anti-corruption, and civil society participation. Wolfowitz concluded that it will be up to Africans most of all to bring about the momentous changes needed to conquer poverty. But as Americans we must be able to say that we did everything we could to give them the hand that they need and deserve.